TRANSFORMATION OF MARKETING MARKETING POLICY OF ENTERPRISES IN THE CONDITIONS OF DIGITALIZATION AND CHANGES IN CONSUMER PRIORITIES: EXPERIENCE OF UKRAINIAN COMPANIES IN 2022-2025 - NEBYLYTSIA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article explores the fundamental aspects of the transformation of marketing policy in Ukrainian enterprises during the period 2022–2025, influenced by digitalization, shifting consumer priorities, and the conditions imposed by a full-scale war. The urgency of the topic stems from the critical need for businesses to rapidly adapt to new economic and social realities. These include disrupted logistics, declining purchasing power, accelerated development of e-commerce, and the growing demand for socially responsible and value-driven brands.The research investigates modern approaches to marketing in the digital environment, emphasizing the key challenges and barriers faced by enterprises in times of crisis. It identifies the most impactful factors driving change in marketing practices, such as heightened expectations for speed and flexibility in service delivery, the need for hyper-personalized communications, and the increasing importance of user-friendly online interactions.Particular focus is placed on the evolution of consumer behavior, highlighting a marked increase in expectations for convenience, immediacy, and responsiveness from brands. In response, the article proposes an adaptive sales policy model named "3K", designed to support business resilience and growth in turbulent conditions. This model is structured around three core pillars: Channels (balancing online and offline customer engagement), Content (ensuring personalized, timely, and relevant communication), and Client Flow (managing the customer journey through robust CRM systems).The "3K" model is tailored to the unique context of the Ukrainian business environment and is particularly suited to the needs of small and medium-sized enterprises (SMEs). It provides a strategic framework for enhancing marketing effectiveness, deepening customer orientation, and achieving sustainable development amid digital transformation and socio-economic instability. The findings of this research hold significant practical value for businesses seeking to remain competitive and responsive in an era defined by constant uncertainty and change.
Keywords: sales; digitalization; marketing; omnicanal strategy; consumer; war; client flow; model 3K